A prospective study of the association between rate of nicotine metabolism and alcohol use in tobacco users in the United States. (1st November 2020) - Roberts, Walter; Marotta, Phillip L.; Verplaetse, Terril L.; Peltier, MacKenzie R.; Burke, Catherine; Ramchandani, Vijay A.; McKee, Sherry A.
Highlights: Rate of nicotine metabolism is a known risk factor for tobacco use disorder. Tobacco users show high rates of harmful alcohol use. Nicotine metabolism speed was associated with alcohol outcomes at 1 year follow up. Rate of nicotine metabolism is a shared risk factor for alcohol and tobacco use. Abstract: Background: Rate of nicotine metabolism has been identified as a biochemical risk factor for nicotine use and dependence; however, its role in alcohol consumption and related outcomes is not well understood. The current research examined nicotine metabolism rate as a risk factor for alcohol use among current tobacco users. We also examined sex differences in these associations. Method: Data were taken from Waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) study, a national longitudinal study of tobacco use and associated health outcomes. The nicotine metabolite ratio (NMR) was calculated as the ratio of trans-3' hydroxycotinine to cotinine in urine samples provided at wave 1. Alcohol use outcomes included past 30-day NIAAA-defined hazardous drinking status, total drinks, and alcohol-related consequences. All analyses controlled for alcohol use at Wave 1. Results: NMR at Wave 1 predicted increased odds of meeting hazardous drinking criteria, adjusted odds ratio (aOR) = 1.14, 95 % CI = 1.06; 1.23, p = 0.001, greater total alcohol consumption amount, adjusted rate ratio (aRR) = 1.21, 95 % CI = 1.12; 1.30, p  <  0.001, and more alcohol consequences, aRR = 1.07, 95 % CI = 1.01; 1.13, p  =  0.018, at wave 2. No significant sex differences were identified. NMR remained a significant predictor of alcohol use in models controlling for severity of nicotine exposure in cigarette smokers. Conclusions: NMR may be a shared risk factor for harmful nicotine and alcohol use that contributes to their co-occurrence.